Studi Literatur: Pengaruh Penerapan Model Pembelajaran Guided Inquiry (GI) terhadap Hasil Belajar Kognitif, Afektif, dan Psikomotor Siswa Sekolah Menengah pada Materi Biologi: (Literature Study: The Effect Of Application Of Guided Inquiry (GI) Learning Models On Cognitive, Affective, And Psychomotor Learning Outcomes Of Middle School Students On Biology Materials) - Mutia Hanifah; Purwanti Pratiwi Purbosari (BIODIK, 2022)
The guided inquiry learning model is a learning model that has the potential to improve student learning outcomes. However, no researchers have conducted a literature study on the effect of applying the guided inquiry learning model on learning outcomes in the cognitive, affective, and psychomotor domains of high school students on biology material. This research was a literature study with a narrative review design. The scientific articles used as research data were 42 articles from the international journal, national journals accredited, national journals unaccredited, proceedings, and repositories. Article validation was carried out by considering freely accessible articles, quality of research methodologies, article topics, article objects, and research references for the last ten years. Data collection techniques through keywords and presented in tabular form. The data analysis technique used descriptive analysis. Based on the literature study, applying the guided inquiry learning model could improve high school students' cognitive, affective, and psychomotor learning outcomes on biology material. Keyword : cognitive, affective, psychomotor learning outcomes, guided inquiry, literature study. Abstrak Model pembelajaran guided inquiry merupakan model pembelajaran yang berpotensi untuk meningkatkan hasil belajar siswa. Akan tetapi, belum ada peneliti yang melakukan kajian literatur mengenai pengaruh penerapan model pembelajaran guided inquiry terhadap hasil belajar ranah kognitif, afektif, dan psikomotor siswa sekolah menengah pada materi biologi. Penelitian ini merupakan penelitian studi literatur dengan desain narrative review. Artikel ilmiah yang digunakan sebagai data penelitian sebanyak 42 artikel yang berasal dari jurnal internasional, jurnal nasional terakreditasi, jurnal nasional tidak terakreditasi, prosiding, dan repository. Validasi artikel dilakukan dengan mempertimbangkan artikel dapat diakses secara bebas, kualitas metodologi penelitian, topik bahasan artikel, objek penelitian artikel, dan dengan referensi 10 tahun terakhir. Teknik pengumpulan data melalui kata kunci dan disajikan dalam bentuk tabel. Teknik analisis data menggunakan analisis deskriptif. Berdasarkan hasil studi literatur, penerapan model pembelajaran guided inquiry dapat meningkatkan hasil belajar kognitif, afektif, dan psikomotor siswa sekolah menengah pada materi biologi. Kata Kunci: hasil belajar kognitif, afektif, psikomotor, guided inquiry, studi literatur